2015
DOI: 10.1007/s00406-015-0604-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and executive function on visuospatial working memory in adult obsessive–compulsive disorder

Abstract: Visuospatial working memory (VSWM) is the ability of the brain to transiently store and manipulate visual information. VSWM deficiencies have been reported in obsessive-compulsive disorder (OCD), but not consistently, perhaps due to variability in task design and clinical patient factors. To explore this variability, this study assessed effects of the design factors task difficulty and executive organizational strategy and of the clinical factors gender, OCD symptom dimension, and duration of illness on VSWM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…Of the 10 studies, three were conducted in the United Kingdom (Dittrich, Johansen, Fineberg, & Inge Landrø, ; Dittrich, Johansen, Inge Landrø, & Fineberg, ; Lawrence et al., ), two in South Korea (Jang et al., ; Shin et al., ), two in Brazil (Pedron et al., ; Pinto et al., ), one in Italy (Martoni, Salgari, Galimberti, Cavallini, & O'Neill, ), one in Japan (Hashimoto et al., ), and one in India (Kashyap, Kumar, Kandavel, & Reddy, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 10 studies, three were conducted in the United Kingdom (Dittrich, Johansen, Fineberg, & Inge Landrø, ; Dittrich, Johansen, Inge Landrø, & Fineberg, ; Lawrence et al., ), two in South Korea (Jang et al., ; Shin et al., ), two in Brazil (Pedron et al., ; Pinto et al., ), one in Italy (Martoni, Salgari, Galimberti, Cavallini, & O'Neill, ), one in Japan (Hashimoto et al., ), and one in India (Kashyap, Kumar, Kandavel, & Reddy, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies contained at least one participant with a co‐occurring tic disorder diagnosis ( n = 1, Shin et al., ; n = 2, Martoni et al., ) and two studies did not provide data on specific comorbidities within their sample (Pedron et al., ; Pinto et al., ). Five studies excluded participants with a co‐occurring depressive disorder, three studies included individuals with a depressive diagnosis but did not provide data on the number of individuals, one study provided percent of the sample with comorbid depression (56.3%, Pinto et al., ), and one study did not provide any data on comorbid depression within the sample (Pedron et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the assumed variability in task design and clinical patient factors responsible for inconsistently reported deficiencies in visuospatial working memory (VSWM) in obsessive-compulsive disorder (OCD), Martoni et al [8] studied effects of design factors task difficulty, the clinical factors gender, OCD symptom dimension, and duration of illness on VSWM. The authors could confirm a previously reported VSWM deficit in OCD, which noteworthy only was significant for females and thus underlines evidence for sexual dimorphism in this disorder.…”
mentioning
confidence: 99%
“…Support for the claim that random generation taxes the central executive comes from studies examining Alzheimer's patients and patients with frontal lobe lesions who display difficulty generating random sequences (Brugger, Monsch, Salmon, & Butters, 1996) and who have difficulty performing two concurrent tasks (Baddeley, Logie, Bressi, Della Sala, & Spinnler, 1986), both of which indicate impairments in the ability to coordinate attentional resources; a function of the central executive (Baddeley, 1996). Research has also linked impairments of central executive functioning to disorders such as attention deficit/hyperactivity disorder (Alderson, Hudec, Patros, & Kasper, 2013) and obsessivecompulsive disorder (Martoni, Salgari, Galimberi, Cavallini, & O'Neill, 2015) in adults, as patients suffering from these disorders displayed a noted lack of executive organization strategies and self-regulation (Hoffman, Schmeichel, & Baddeley, 2012).…”
Section: The Central Executivementioning
confidence: 99%